Combined metabolomic and transcriptomic analysis reveals key components of OsCIPK17 overexpression improves drought tolerance in rice - Lu, Shuai; Chen, Yaoyu; Wang, Surong; Han, Binying; Zhao, Chenglei; Xue, Penghui; Zhang, Yue; Fang, Hui; Wang, Baohua; Cao, Yunying (Frontiers in Plant Science, 2023)
Oryza Sativa is one of the most important food crops in China, which is easily affected by drought during its growth and development. As a member of the calcium signaling pathway, CBL-interacting protein kinase (CIPK) plays an important role in plant growth and development as well as environmental stress. However, there is no report on the function and mechanism of OsCIPK17 in rice drought resistance. We combined transcriptional and metabonomic analysis to clarify the specific mechanism of OsCIPK17 in response to rice drought tolerance. The results showed that OsCIPK17 improved drought resistance of rice by regulating deep roots under drought stress; Response to drought by regulating the energy metabolism pathway and controlling the accumulation of citric acid in the tricarboxylic acid (TCA) cycle; Our exogenous experiments also proved that OsCIPK17 responds to citric acid, and this process involves the auxin metabolism pathway; Exogenous citric acid can improve the drought resistance of overexpression plants. Our research reveals that OsCIPK17 positively regulates rice drought resistance and participates in the accumulation of citric acid in the TCA cycle, providing new insights for rice drought resistance.